Analisis Kemampuan Komunikasi Matematis ditinjau dari Sociomathematical Norms - Saputri, Khulyatin Dyah; Maarif, Samsul (Universitas Muria Kudus, 2022)
Sociomathematical norms are reflected in the activities of mathematics study in class. The purpose of this study was to study and understand the mathematical communication ability both writing and oral of middle-school students to work on statistical problem based on sociomathematical norms. This type of research method is a qualitative descriptive using case study analyzed from the given instruments. The subjects of this research are the ninth grade school year 2021/2022 of a public middle-school in Jakarta. The data collected using questionnaire and questions. The result of the research shows that the students in high, moderate, and low category have different mathematical communication ability and directly proportional to the sociomathematical norms category. Furthermore, the mathematical communication ability of the subjects in oral and writing are showing the similarity on both abilities. Nevertheless, the students’ different mathematical ability in the same sociomathematical norms category could happen which obtained from a mathematical insight outside the school study.